Effect of Oral and Vaginal Hormonal Contraceptives on Inflammatory Blood Biomarkers - Afshin A. Divani; Xianghua Luo; Yvonne H. Datta; James D. Flaherty; Angela Panoskaltsis-Mortari (Hindawi Limited, 2015)
The use of combined hormonal contraceptives has been reported to increase the level of C-reactive protein (CRP). We assessed the effect of hormonal contraceptive use on inflammatory cytokines including CRP, monocyte chemotactic protein-1, soluble tumor necrosis factor (sTNF), interleukin-6 (IL-6), and soluble CD40 ligand. We used 79 female subjects (19 to 30 years old) who were combined oral contraceptives users (n=29), combined vaginal contraceptive users (n=20), and nonusers (n=30) with CRP values of ≤1 (n=46) or ≥3 (n=33). Information on medical history, physical activities, and dietary and sleeping habits were collected. Both oral and vaginal contraceptive users had higher levels of CRP (P<0.0001), compared to nonusers. Only oral contraceptive users exhibited elevated sCD40L (P<0.01). When comparing the groups with CRP ≤ 1 and CRP ≥ 3, levels of IL-6 and sTNF-RI were positively correlated with CRP among oral contraceptive users. We did not observe the same elevation for other inflammatory biomarkers for the CRP ≥ 3 group among vaginal contraceptive users. The clear cause of elevation in CRP level due to the use of different hormonal contraceptive formulations and methods is not well understood. Longitudinal studies with larger sample size are required to better assess the true cause of CRP elevation among hormonal contraceptive users.